Membangun Sinergi Lintas Generasi: Strategi Kolaboratif untuk Meningkatkan Kinerja Organisasi di Era Digital - Alfa Santoso Budiwidjojo Putra (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This scholarly oration discusses the importance of building cross-generational synergy in modern organizations in the digital era. With a workforce comprising four main generations (Baby Boomers, Generation X, Millennials, and Generation Z), organizations face challenges and opportunities in fostering effective collaboration. The oration explores concrete strategies to enhance team synergy and performance, including mentoring programs, cross-generational team formation, and generational awareness training. The role of digital technology in facilitating collaboration is also discussed, along with successful examples of organizations that have built cross-generational synergy. Implications for education and leadership development are outlined, emphasizing the importance of adapting curricula to prepare future leaders capable of effectively managing cross-generational teams. The oration also addresses challenges such as differences in values, work styles, and expectations across generations, as well as stereotypes and prejudices that can hinder collaboration. However, these differences are also viewed as opportunities for two-way learning and skill exchange. The importance of creating an inclusive work environment that values diversity is highlighted. Finally, the oration emphasizes that building cross-generational synergy is a valuable investment for the future of organizations, capable of creating a collaborative, innovative, and sustainable work environment.